Analisis Putusan Pemidanaan dan Putusan Lepas dari Segala Tuntutan Tindak Pidana Ujaran Kebencian yang Dilakukan Aktivis Lingkungan (Studi Putusan PN Nomor 14/Pid.Sus/2024/PN.Jpa dan Putusan PT Nomor 374/Pid.Sus/2024/PT.Smg) - Situmorang, Agnes Marsella; Lubis, Rafiqoh; Marlina, Marlina (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Environmental activists in Indonesia often face criminalization when voicing public interests, despite legal protection in Article 66 of Law No. 32 of 2009. This study discusses the differences in judges' considerations in 2 (two) decisions related to hate speech by an environmental activist, namely the District Court Decision No. 14/Pid.Sus/2024/PN.Jpa which imposed a criminal sentence, and the High Court Decision No. 374/Pid.Sus/2024/PT.Smg which overturned the decision. The research method used is normative juridical. The results of this study indicate that the regulation of hate speech is contained in Article 28 paragraph 2 in conjunction with Article 45A paragraph 2 of Law No. 1 of 2024, and the evidentiary system in Indonesia follows the negative system according to the law based on Article 183 of the Criminal Procedure Code. The difference in decisions is caused by different assessments of evidence: the District Court emphasizes formal aspects, while the High Court considers the context of protection for environmental activists.